Maslow, Basic Needs and Contemporary Teacher Training Issues - , Michael F. Shaughnessy, Bryan Moffitt, Mia Cordova (Archives of Current Research International, 2018)
The work of Abraham Maslow and his hierarchy of needs has been referred to for decades. However, his ideas and concepts regarding basic needs still require review and reflection in this current zeitgeist. This paper reviews some of the issues confronting teachers relative to Maslow's basic needs.